Trends in Restructuring NMS Regional Economies as Responses to Transformation, Crisis and EU Membership. A Spotlight on Suceava County - Bogdan-Vasile Ileanu; Zizi Goschin; Daniela-Luminita Constantin; Constantin Mitrut; Amalia Cristescu (European Regional Science Association (ERSA), 2014)
The current research has concentrated on the following questions: What are the trends in restructuring Suceava's economy and which regional development factors were the most important (exogenous, endogenous, structural, socio-political ones, etc.)? Which is the relationship between social disparities and economic growth? Which regional/local policies proved to be the most successful for economic regeneration? How important was the external intervention for county's development? In order to respond these questions in-depth interviews were carried out with representatives of county and city office, national and regional authorities, Regional Development Agency, chambers of commerce, business associations, higher education institutions, and implementing authorities. Also, statistical socio-economic data were gathered and processed and strategic documents on development strategy, as well as various reports on evaluations of public policies have been studied. The study has been conducted within the GRINCOH FP7 project.
Keywords: R11; R38; 330; restructuring; transition; crisis; EU financial assistance; Romania; Suceava county